IMPLIKASI UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH TERHADAP PENGELOLAAN BAHAN GALIAN MINERAL BUKAN LOGAM DAN BATUAN - I Made Sugita (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Abstract One aspect that was also affected by the issuance of Law Number 23 of 2014 concerning Regional Government was the management of mining of non-metallic minerals and rocks, which before the issuance of Law Number 23 of 2014 concerning Regional Government was managed by the district/city government, then when This is the authority of the provincial government. The purpose of this research is to find out the implications of Law Number 23 of 2014 concerning Regional Government on the management of non-metal mineral minerals and rocks. Writing this article is done using the method of literature study. Literature research was carried out using policy conceptions, laws and regulations, theory or doctrine, and conceptual thinking and preliminary research related to the object of study in this study. The results of this study indicate that the management of non-metallic mineral materials and rocks, that currently Law Number 23 of 2014 has explicitly handed over as provincial government affairs, there is no longer the authority of district/city governments in terms of managing non-metallic mineral materials and rocks. When compared with Law Number 32 of 2004 that the management of non-metallic minerals and rocks is carried out proportionally and in more harmony or in sync with other laws and regulations. Proportionally means that there is authority that belongs to the district/city if it is actually in the district/city area which can be used for the greatest possible welfare of the people or to increase PAD, but there is also the authority of the provincial government, namely if mining c which covers cross-regency/ city ​​or located in the sea area between 4-12 nautical miles in one province. Changes in the authority to manage non-metallic mineral materials and rocks apart from creating conflicts with other laws and regulations, in a number of cases have actually created difficulties for local governments in implementing them, namely for regions that have difficulty in reaching them. metal and rock from the district/city government to the provincial government becomes ineffective and actually weakens the government itself, both in terms of licensing services and in terms of supervision. Keywords: Implications, Management and Non-metal mineral materials and rocks